THE USE OF SQ4R FOR IMPROVING READING SKILL: HOW SHOULD IT BE IMPLEMENTED? - Dian Tri Riska Ekawati; Dzulfikri Dzulfikri; Saiyidi Hasbullah (Institut Dirosat Islamiyah Al-Amien Prenduan, 2020)
For senior high school students, understanding literature has become a struggle. Impaired vocabulary and prior knowledge, grammatical flaws, and poor reading methods were all important factors in reading. As a result, this study aims to use SQ4R as a technique for overcoming learners’ difficulties in learning reading, particularly those studying English in SMKN 1 Bakung. SQ4R is one of the most widely used acronyms (Survey, Question, Read, Recite, Review, and Reflect). The SQ4R reading method is aimed to engage kids in reading activities, encourage them to enjoy reading, and enhance their academic achievement as a result. Students should apply what they already know to assist them learn new material, according to SQ4R. This study employs Classroom Action Research (CAR) at XI TKJ, using data obtained from two instruments: a post-test and observation sheets. A total of 26 students participated in the study. The findings of this study show that after being taught the approach, students’ reading ability improves. The students acquire an average score of 55.4 in pre-test. Then, their average score increases to 63.3 in the first cycle. The average score climbs to 73.3 average scores in the second round. The success criteria for this study were that 75% of the students (19 students) got a score of 65.